Analisis Strategi Korporasi "PT Tugu Pratama Indonesia" Terhadap Industri Asuransi Kerugian - , Agung Hirawan, SE., Mudrajad Kuncoro, Prof., Dr., M.Soc.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study planned to examine: corporate strategy of PT. Tugu Pratama Indonesia in the insurance industry using structure, conduct, performance analysis (SCP). Industrial structure is obtained through sorting insurance companies who had occupied thirty-five in acquisition premiums for five years and are grouped based on personal and corporate business line. Conduct in the analysis based on defined strategic variables, namely: product diversification (DIVER), firm size (LSIZE), the ratio of costs (EXRATIO), the proportion of reinsurance (PREINS), financial leverage (Lever), investment strategy (PSTOCK). Performance analysis based on a strategic variable: combine ratio (COMB), market share (MSHARE) and return on equity (ROE). The distinction test of conduct and performance of insurance industry and the company are observed, used MANOVA analysis. Meanwhile, to explain the classification of companies in the insurance industry based on the structure, conduct and performance strategic variables used discriminant analysis. Results of sorting and grouping of the firms in the industry based on personal and corporate business line can be proved through booked premium structure analysis. MANOVA analysis proves the existence of differences in conduct and performance of companies in the insurance industry based on personal, corporate lines of business groups, and against companies that were observed. Classification of companies and business lines in the industry groups can be explained through discriminant test results are interpreted as a pattern of generic strategies based on the measured variables.